A multivariate approach to explore the volatolomic and sensory profiles of craft Italian Grape Ale beers produced with novel Saccharomyces cerevisiae strains - Pietrafesa, Rocchina; Siesto, Gabriella; Tufariello, Maria; Palombi, Lorenzo; Baiano, Antonietta; Gerardi, Carmela; Braghieri, Ada; Genovese, Francesco; Grieco, Francesco; Capece, Angela (Frontiers in Microbiology, 2023)
This study investigated the influence of three Saccharomyces cerevisiae strains, selected from different matrices -CHE-3 (cherry), P4 (sourdough) and TA4-10 (grape must) -on chemical, volatolomic, and sensory profiles of IGA (characteristics of Italian Grape Ale (IGA) beers. obtained at microbrewery scale. A multidisciplinary approach, combining sensory and chemicalresults from analysis based on HPLC-DAD, GC-MS, GC-FID and spectrophotometer detectionsof chemical, volatile and organoleptic profiles of the beers, was adopted to underline the relationships between yeast starter and the quality of final products. HPLC data highlightedDetection Volatile Organic Compounds (VOCs) by Gas-Chromatography coupled with Mass Spectrometry (GC-MS) after extraction carried out by head-space micro-extraction (HS-SPME) revealed that the ability of all the tested yeast strains to metabolize maltose and glucose. P4beer obtained by P4 strain differed from the This is a provisional file, not the final typeset article others for its higher concentrations of esters, alcohols, and terpenes as demonstratedconfirmed by PCA (Principal Component Analysis) and Cluster heatmap. ContrarilyFurthermore, sensorial analysis and consumer test showed that this sample differed from others by more pronounced notes of "fruity smell and floral" and "olfactory finesse", and it was the most appreciated beer for smell, taste, and overall quality. Conversely, CHE-3 was the sample with the lowest concentrations of the identified volatiles. P4 beer differed by more pronounced notes of "fruity smell and floral" and "olfactory finesse". CHE-3 and and, together TA4-10, showed the highest scores for smoked, yeast, malt, and hop notes, while effervescence and spices smell predominated in the control. A PLSC analysis was carried out to characterize the relation between volatiles, odor and visive attributes.. As far as we know, these are the first results on the application of microbial cross-overindigenous S. cerevisiae strains in the production of craft IGA beers analyzed through a complex multivariate approach.